Ethical challenges experienced by care home staff during COVID-19 pandemic. (December 2022) - Chan, Helen YL; Zhao, Ya-Yi; Liu, Li; Chong, Yuen-Yu; Cheng, Ho-Yu; Chien, Wai-Tong
Background: Care homes have been disproportionately affected during the COVID-19 pandemic. Practical challenges of enacting infection control measures in care home settings have been widely reported, but little is known about the ethical concerns of care home staff during the implementation of such measures. . Objectives: To understand the ethical challenges perceived by care home staff during the early months of the COVID-19 pandemic. Research design: An exploratory qualitative study. Participants and research context: A purposive sample of 15 care home staff in different roles and ranks in Hong Kong was recruited to take part in semi-structured interviews between June and August 2020. Ethical considerations: Ethical approval for this study was obtained. Participation was voluntary and anonymous. Participants had the right to withdraw from the study at any time without reprisal. Findings: Three themes were identified: unclear legitimacy regarding infection control measures, limited autonomy in choices over infection control measures and inevitable harms to residents' well-being. While the participants expected that they would have legitimated power to implement infection control measures, they were resistant when their right to self-determination of testing and vaccination was infringed. They also felt trapped between ethical duties to protect care home residents from infection risk and the anticipated detrimental effects of infection control measures. Conclusions: The findings of this study reveal tensions among the ethical obligations of care home staff in response to a public health emergency. They highlight the importance of strengthening ethical sensitivity and ethical leadership in identifying and resolving the challenges of pandemic responses.